2022
DOI: 10.1093/nar/gkac023
|View full text |Cite
|
Sign up to set email alerts
|

POLIE suppresses telomerase-mediated telomere G-strand extension and helps ensure proper telomere C-strand synthesis in trypanosomes

Abstract: Trypanosoma brucei causes human African trypanosomiasis and sequentially expresses distinct VSGs, its major surface antigen, to achieve host immune evasion. VSGs are monoallelically expressed from subtelomeric loci, and telomere proteins regulate VSG monoallelic expression and VSG switching. T. brucei telomerase is essential for telomere maintenance, but no regulators of telomerase have been identified. T. brucei appears to lack OB fold-containing telomere-specific ssDNA binding factors that are critical for c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(36 citation statements)
references
References 87 publications
0
36
0
Order By: Relevance
“…DNA double strand breaks (DSBs) at the active VSG vicinity has been shown to be a potent trigger for VSG switching (Alsford et al, 2009;Boothroyd et al, 2009;Glover et al, 2013;Li, 2021), as homology directed DNA recombination (HDR) repairs DSBs most accurately (Jasin and Rothstein, 2013;Haber, 2018;Wright et al, 2018), and HDR is very active in T. brucei (McCulloch and Barry, 1999;Robinson et al, 1999;Conway et al, 2002a;Barnes and McCulloch, 2007;Glover et al, 2008;Marin et al, 2018). Consistently, for known essential T. brucei telomere proteins, a transient depletion of the protein leads to an increased amount of DNA breaks at the telomere and subtelomere and more frequent VSG switching, indicating that these telomere proteins help maintain the telomere stability and suppress VSG switching (Jehi et al, 2014a;Jehi et al, 2014b;Jehi et al, 2016;Nanavaty et al, 2017;Afrin et al, 2020a;Afrin et al, 2020b;Saha et al, 2021;Rabbani et al, 2022;Gaurav et al, 2023). Furthermore, in telomerase null cells where the active ES-adjacent telomere is extremely short, a significant increase in the VSG switching rate is observed (Hovel-Miner et al, 2012).…”
Section: Introductionmentioning
confidence: 80%
“…DNA double strand breaks (DSBs) at the active VSG vicinity has been shown to be a potent trigger for VSG switching (Alsford et al, 2009;Boothroyd et al, 2009;Glover et al, 2013;Li, 2021), as homology directed DNA recombination (HDR) repairs DSBs most accurately (Jasin and Rothstein, 2013;Haber, 2018;Wright et al, 2018), and HDR is very active in T. brucei (McCulloch and Barry, 1999;Robinson et al, 1999;Conway et al, 2002a;Barnes and McCulloch, 2007;Glover et al, 2008;Marin et al, 2018). Consistently, for known essential T. brucei telomere proteins, a transient depletion of the protein leads to an increased amount of DNA breaks at the telomere and subtelomere and more frequent VSG switching, indicating that these telomere proteins help maintain the telomere stability and suppress VSG switching (Jehi et al, 2014a;Jehi et al, 2014b;Jehi et al, 2016;Nanavaty et al, 2017;Afrin et al, 2020a;Afrin et al, 2020b;Saha et al, 2021;Rabbani et al, 2022;Gaurav et al, 2023). Furthermore, in telomerase null cells where the active ES-adjacent telomere is extremely short, a significant increase in the VSG switching rate is observed (Hovel-Miner et al, 2012).…”
Section: Introductionmentioning
confidence: 80%
“…The RNA component of T. brucei telomerase (TbTR) has a unique structure and sequence composition compared to higher eukaryotes (Sandhu et al, 2013;Podlevsky et al, 2016;Dey et al, 2021). Our recent study on TbTR suggests mechanistic differences in telomere maintenance between T. brucei and higher eukaryotes (Dey et al, 2021;Rabbani et al, 2022, underscoring the importance of investigating the functional interactome of T. brucei telomerase. Previous proteomic studies on ciliated single-cell protozoan Tetrahymena identified several RNA binding proteins, including p65 that copurifies with TR and TERT and promotes proper folding of TR for telomerase holoenzyme assembly and activity (Witkin and Collins, 2004;Berman et al, 2010;Singh et al, 2012;Upton et al, 2017;He et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…In cells where the TERT protein has been deleted ( Tb TERT −/− ), extremely short telomeres adjacent to the active ES leads to an increase in VSG switching frequency ( Dreesen and Cross, 2006 ; Hovel-Miner et al, 2012 ). Telomeric binding proteins have also been shown to affect VSG silencing and switching ( Yang et al, 2009 ; Benmerzouga et al, 2013 ; Jehi et al, 2014 ; Jehi et al, 2016 ; Nanavaty et al, 2017 ; Afrin et al, 2020 ; Rabbani et al, 2022 ). Telomerase mediated telomere maintenance in T. brucei is required for the maintenance of subtelomeric VSG genes.…”
Section: Introductionmentioning
confidence: 99%
“…PolIE is a putative translesion polymerase localized at the nuclear periphery, and its depletion leads to deregulation of VSG expression and aberrant chromosome segregation. Furthermore, cells depleted of PolIE have longer 3’ overhangs, suggesting that PolIE is also involved in telomerase regulation (34).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cells depleted of PolIE have longer 3' overhangs, suggesting that PolIE is also involved in telomerase regulation (34).…”
Section: Introductionmentioning
confidence: 99%